"Greener" Coupling of Poly(methyl methacrylate) and Poly(methyl acrylate) Chains using Activators Generated by Electron Transfer and Radical Traps. Issue 13 (8th June 2020) - Xia, Katherine; Rubaie, Alia; Johnson, Brendan; Tillman, Eric S.
Abstract: Monobrominated versions of poly(methyl methacrylate) (PMMABr) and poly(methyl acrylate) (PMABr) are prepared by atom transfer radical polymerization and subjected to a variety of chain end‐coupling reactions, with the goal of achieving high extents of coupling with minimal metal content. By using atom transfer radical coupling (ATRC) with radical trap assistance in conjunction with activators generated by electron transfer, high extents of coupling ( X c ) could be achieved for both polymer classes without requiring copper(I) as an initial reactant, and replacing elemental copper with environmentally benign reducing agents ( X c > 0.85). Specifically, the highest extents of coupling are observed with ascorbic acid as the reducing agent along with copper(II) bromide as the pre‐catalyst. Overall, similar extents of coupling are observed while using ≈1% of the total metal of a traditional ATRC reaction for PMABr and ≈3% for PMMABr. Abstract : Activators generated by electron transfer are used to produce macro‐radicals from brominated versions of poly(methyl methacrylate) and poly(methacrylate). When carried out in the presence of a nitroso radical trap (specific to each polymer type), substantial dimerization occurs using only a small fraction of the metal catalyst typical of atom transfer radical‐type coupling reactions.